Preparation method of high-toughness double-phase high-entropy alloy

By adding Ti elements to the FCC structure high-entropy alloy and performing high-temperature homogenization and isothermal quenching, the two-phase structure morphology of the alloy is regulated, and the problem of strength-plastic mismatch of high-entropy alloys is solved, and its tensile strength and yield strength are significantly improved.

CN119663089AInactive Publication Date: 2025-03-21SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411885867.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

FCC structural high entropy alloys exhibit severe strength-plastic mismatch, especially lower room temperature yield strength, limiting their engineering applications.

Method used

By adding the alloying element Ti, the solid solution strengthening, fine crystal strengthening and second phase strengthening of the high-entropy alloy are promoted, and the Fe35Ni35Cr20Mn10Ti6 high-entropy alloy is subjected to high-temperature homogenization treatment + isothermal quenching treatment to regulate the biphasic structure of the alloy.

Benefits of technology

The tensile strength and yield strength of high entropy alloys were significantly improved, the yield strength was improved by 336%, and the high elongation of 14.0% was maintained, achieving toughening.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663089A_ABST
    Figure CN119663089A_ABST
Patent Text Reader

Abstract

The invention discloses a high-toughness double-phase high-entropy alloy and a preparation method thereof, and belongs to the technical field of metal materials and manufacturing. The preparation raw materials of the high-entropy alloy are Fe, Ni, Cr, Mn and Ti metal particles or block ingots, and the preparation method specifically comprises the following steps: weighing the metal particles or block ingots according to a set proportion, and smelting by adopting a vacuum electric arc furnace and a vacuum induction furnace including but not limited to the vacuum electric arc furnace and the vacuum induction furnace. The prepared high-entropy alloy cast ingot is subjected to high-temperature homogenization treatment in a heat treatment furnace to obtain a single-phase structure, then a sample is subjected to isothermal quenching treatment, a strengthening phase is separated out, the double-phase high-entropy alloy is formed, on the premise that high plasticity is kept, high strength is achieved, and strengthening and toughening are achieved. The prepared high-entropy alloy has excellent comprehensive mechanical properties, the preparation process is simple, industrial large-scale production is facilitated, and further development of the high-entropy alloy in actual production can be promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-strength and high-toughness dual-phase high-entropy alloy, and belongs to the technical field of metal materials and preparation thereof. Background Art

[0002] The design concept of traditional alloys is to select the main components based on specific performance requirements, and further use alloy additives to impart secondary properties without sacrificing the main properties. With the development of science and technology industry, traditional metal and alloy materials are facing many bottlenecks, so there is an urgent need to design and develop new high-performance structural alloys. At the beginning of the 21st century, Taiwan scholar Ye Junwei broke through the traditional alloy design concept and took the lead in proposing the design idea of ​​"high entropy alloy". The unique and novel alloy design concept gives high entropy alloys different properties from traditional alloys, such as high entropy effect, lattice distortion effect, slow diffusion effect and "cocktail" effect. In turn, these unique alloy properties give it excellent properties, such as high strength, high hardness, high wear resistance, excellent oxidation resistance, excellent corrosion resistance and high temperature softening resistance. This makes high entropy alloys show huge application potential and market in the fields of structural materials and functional materials, attracting widespread attention from researchers.

[0003] The early research focus of high entropy alloys was on alloy composition design, that is, the influence of the type and content of component elements on the microstructure and properties of high entropy alloys. Researchers have optimized the performance of alloys through reasonable element ratios, even surpassing traditional alloy materials. In recent years, the number of alloy types explored has increased, and the relationship between the microstructure and performance of high entropy alloys has been gradually explored, but the simple macroscopic component allocation can no longer support the further pursuit of high performance. As an important branch of the high entropy alloy system, face-centered cubic (FCC) structured high entropy alloys have a series of excellent properties such as high damage tolerance, good radiation resistance, high wear resistance, and corrosion resistance, and can be used as ideal engineering structural materials. However, FCC structured high entropy alloys show a serious mismatch between strength and plasticity, especially the low room temperature yield strength, which greatly limits the practical engineering application of FCC structured high entropy alloys. Therefore, it is of great significance to develop high entropy alloys with good comprehensive mechanical properties.

[0004] In recent years, researchers have focused on the exploration of trace element addition and its heat treatment mechanism. The effect of Cu alloying on the mechanical properties of Fe20Co30Ni10Cr20Mn20 high entropy alloy was studied. It was found that when the addition amount was 4.76%, the yield strength increased from 217MPa to 397MPa, and the plasticity decreased from 82% to 56%. In addition, the addition of Ta element to CoCrFeNi high entropy alloy promotes the formation of Laves phase strengthening matrix in the alloy, which significantly improves the compressive strength of the alloy. By adopting high temperature solid solution and furnace cooling heat treatment process, nano-sized spherical precipitates were successfully obtained in Al0.3CoCrCu0.5FeNi high entropy alloy, which effectively improved the strength and toughness of the alloy. By aging the AlCoCrFeNi2.1 high entropy alloy, the hard B2 phase is evenly distributed on the soft FCC matrix phase, resulting in a significant improvement in the strength and toughness of the alloy. In summary, the introduction of the second phase can effectively improve the comprehensive mechanical properties of FCC high entropy alloys, but the second phase precipitated in the high entropy alloy will inherit the multi-principal element and hysteresis diffusion characteristics of the high entropy alloy. Compared with the second phase in the traditional alloy, its composition, structure and distribution are relatively complex. Regulating the size, morphology, distribution and volume fraction of the second phase is crucial to improving the mechanical properties of precipitation-strengthened high entropy alloys. Studies have shown that the elemental composition and microstructure of the precipitated phase can be adjusted by changing the heat treatment process. The face-centered cubic Fe35Ni35Cr20Mn10 high entropy alloy has excellent ductility and excellent corrosion resistance, but its yield strength is only 205MPa, which limits its engineering application. It is scientific to design a high entropy alloy with a dual-phase structure with a soft and hard phase effect by alloying and improving the heat treatment process to improve its comprehensive mechanical properties. Summary of the invention

[0005] Technical problem: In view of the above-mentioned prior art, the present invention provides a high-strength and toughness dual-phase high-entropy alloy and a preparation method thereof. The present invention promotes the solid solution strengthening, fine grain strengthening and second phase strengthening of the high-entropy alloy by adding the alloying element Ti, and at the same time performs high-temperature homogenization treatment + isothermal quenching treatment on the Fe35Ni35Cr20Mn10Ti6 high-entropy alloy, effectively regulating the dual-phase microstructure of the alloy, thereby improving the comprehensive mechanical properties of the high-entropy alloy.

[0006] Technical solution: The high-strength and toughness dual-phase high-entropy alloy described in the present invention contains metal elements Fe, Ni, Cr, Mn and Ti.

[0007] The high-strength and toughness dual-phase high-entropy alloy is expressed as Fe35Ni35Cr20Mn10Ti6, and the numbers represent the molar ratio of each element.

[0008] The alloy has a tensile strength of 1043 MPa, a yield strength of 876 MPa, and an elongation of 14.0%.

[0009] The preparation method of the high-strength and toughness dual-phase high-entropy alloy of the present invention comprises the following steps:

[0010] Step 1: weigh the mass of each element and prepare the ingredients according to the alloy element molar ratio of Fe:Ni:Cr:Mn:Ti=(34~36):(34~36):(19~21):(9~11):(5~7);

[0011] Step 2: placing the raw materials prepared in step 1 into a vacuum arc furnace in a high-purity argon environment for smelting, or smelting in a vacuum induction furnace, and cooling and solidifying in a mold to obtain an alloy ingot;

[0012] Step 3: performing high temperature homogenization treatment on the alloy ingot smelted in step 2;

[0013] Step 4: The alloy ingot subjected to high temperature homogenization treatment in step 3 is rapidly cooled from the homogenization temperature to the set temperature for isothermal quenching treatment, and then water quenched to room temperature after a specified time to obtain a high-strength and toughness dual-phase high-entropy alloy.

[0014] In step 2, the casting mold includes but is not limited to a copper mold.

[0015] In step 3, the temperature of the high temperature homogenization treatment is 1050-1150° C., the insulation time is 15-25 hours, and the gas environment is air.

[0016] In step 4, the set temperature is 650-750°C and the holding time is 0.5-1.5h.

[0017] Beneficial effects: (1) The present invention performs high-temperature homogenization treatment + isothermal quenching treatment on the high-entropy alloy ingot, the process is simple, and the preparation cost is effectively reduced; (2) Arc furnace and induction furnace smelting are the most widely used alloy smelting process routes at present, the method is simple and easy to operate; (3) The dual-phase high-entropy alloy prepared by the present invention has high tensile strength and yield strength while maintaining a high elongation, achieving toughness and can promote the further development of high-entropy alloys in actual production. The tensile strength is 1043MPa, the yield strength is 876MPa, the yield strength is increased by 336%, and the high elongation of 14.0% is maintained; its technical indicators are greatly improved compared with the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the electron microscope microstructure of the cast Fe35Ni35Cr20Mn10 high entropy alloy;

[0019] Figure 2 This is the electron microscope microstructure of the cast Fe35Ni35Cr20Mn10Ti6 high entropy alloy;

[0020] Figure 3 This is the electron microscope microstructure of the high-temperature homogenized Fe35Ni35Cr20Mn10Ti6 high entropy alloy;

[0021] Figure 4 The electron microscope microstructure of Fe35Ni35Cr20Mn10Ti6 high entropy alloy isothermally quenched at 700℃-1h;

[0022] Figure 5 It is a comparison diagram of the tensile engineering stress-engineering strain curves of the high entropy alloys of Examples 1 to 5. DETAILED DESCRIPTION

[0023] Example 1

[0024] A preparation method of Fe35Ni35Cr20Mn10 high entropy alloy, the specific steps are as follows:

[0025] (1) using fine sandpaper to remove the oxide scale on the surface of Fe, Ni, Cr and Mn metal particles respectively, and then using anhydrous ethanol to perform ultrasonic cleaning to obtain clean metal particles; weighing and mixing the raw materials according to the molar ratio of Fe:Ni:Cr:Mn:Ti=(34-36):(34-36):(19-21):(9-11):(5-7);

[0026] (2) The mixed raw materials weighed in step (1) are repeatedly melted in a vacuum arc furnace (in a high-purity argon environment), and cooled and solidified in a copper mold to obtain an alloy ingot.

[0027] Example 2

[0028] A method for preparing a Fe35Ni35Cr20Mn10Ti6 high entropy alloy, the specific steps are as follows:

[0029] (1) using fine sandpaper to remove the oxide scale on the surface of Fe, Ni, Cr, Mn and Ti metal particles respectively, and then using anhydrous ethanol to perform ultrasonic cleaning to obtain clean metal particles; weighing and mixing the raw materials according to the molar ratio of Fe:Ni:Cr:Mn:Ti=(34-36):(34-36):(19-21):(9-11):(5-7);

[0030] (2) The mixed raw materials weighed in step (1) are repeatedly melted in a vacuum arc furnace (in a high-purity argon environment), and cooled and solidified in a copper mold to obtain an alloy ingot.

[0031] Example 3

[0032] A preparation method for strengthening and toughening Fe35Ni35Cr20Mn10Ti6 high entropy alloy, the specific steps are as follows:

[0033] (1) using fine sandpaper to remove the oxide scale on the surface of Fe, Ni, Cr, Mn and Ti metal particles respectively, and then using anhydrous ethanol to perform ultrasonic cleaning to obtain clean metal particles; weighing and mixing the raw materials according to the molar ratio of Fe:Ni:Cr:Mn:Ti=(34-36):(34-36):(19-21):(9-11):(5-7);

[0034] (2) repeatedly melting the mixed raw materials weighed in step (1) in a vacuum arc furnace (in a high-purity argon environment), and cooling and solidifying them in a copper mold to obtain an alloy ingot;

[0035] (3) The alloy ingot obtained in step (2) is subjected to a high-temperature homogenization treatment at 1100° C. for 20 h, and then taken out and water quenched to room temperature to obtain a high-temperature homogenized high-entropy alloy.

[0036] Example 4

[0037] A method for preparing a high-strength and high-toughness dual-phase high-entropy alloy, the specific steps are as follows:

[0038] (1) using fine sandpaper to remove the oxide scale on the surface of Fe, Ni, Cr, Mn and Ti metal particles respectively, and then using anhydrous ethanol to perform ultrasonic cleaning to obtain clean metal particles; weighing and mixing the raw materials according to the molar ratio of Fe:Ni:Cr:Mn:Ti=(34-36):(34-36):(19-21):(9-11):(5-7);

[0039] (2) repeatedly melting the mixed raw materials weighed in step (1) in a vacuum arc furnace (in a high-purity argon environment), and cooling and solidifying them in a copper mold to obtain an alloy ingot;

[0040] (3) The alloy ingot obtained in step (2) is subjected to a high-temperature homogenization treatment at 1100°C for 20 h, and then quickly transferred to a heat treatment furnace at 700°C for isothermal quenching treatment. The holding time is 0.5 h, 1 h, and 4 h. Finally, the ingot is taken out and water quenched to room temperature to obtain an isothermal quenched high-entropy alloy.

[0041] Example 5

[0042] A method for preparing a high-strength and high-toughness dual-phase high-entropy alloy, the specific steps are as follows:

[0043] (1) using fine sandpaper to remove the oxide scale on the surface of Fe, Ni, Cr, Mn and Ti metal particles respectively, and then using anhydrous ethanol to perform ultrasonic cleaning to obtain clean metal particles; weighing and mixing the raw materials according to the molar ratio of Fe:Ni:Cr:Mn:Ti=(34-36):(34-36):(19-21):(9-11):(5-7);

[0044] (2) repeatedly melting the mixed raw materials weighed in step (1) in a high vacuum arc furnace (in a high-purity argon environment), and cooling and solidifying them in a copper mold to obtain an alloy ingot;

[0045] (3) The alloy ingot obtained in step (2) is subjected to a high-temperature homogenization treatment at 1100°C for 20 h, and then quickly transferred to a constant temperature heat treatment furnace for isothermal quenching treatment at 600°C for 1 h, 800°C for 1 h, and 900°C for 1 h, respectively, and finally taken out and water quenched to room temperature to obtain an isothermal quenched high entropy alloy.

[0046] Experimental results:

[0047] The high entropy alloy prepared above was coarsely ground with sandpaper of different types, and then finely ground to #2000, and then mechanically polished until there were no obvious scratches on the surface. The alloy was corroded with a metallographic corrosive agent, and its microstructure was observed using a scanning electron microscope. Figure 1 As shown, the cast Fe35Ni35Cr20Mn10 high entropy alloy is a single-phase structure; Figure 2 As shown, the cast Fe35Ni35Cr20Mn10Ti6 high entropy alloy shows a typical dendritic structure, which is composed of gray dendritic structure, white and black interdendritic structure; Figure 3 As shown in Figure 2, the Fe35Ni35Cr20Mn10Ti6 high entropy alloy after high temperature homogenization heat treatment presents a single-phase structure, and the secondary phase is completely integrated into the matrix; Figure 4 As shown in the figure, a large number of rod-shaped secondary phases are produced in the sample after high-temperature homogenization treatment at 1100℃×20h + isothermal quenching at 700℃×1h. The softer matrix phase and the sufficient fraction of harder second phase can effectively coordinate the strengthening and toughening.

[0048] The high entropy alloy prepared above was subjected to room temperature tensile performance test, and the tensile curve is as follows: Figure 5 The mechanical properties are shown in Table 1. The tensile strength of the cast Fe35Ni35Cr20Mn10 high entropy alloy is 413MPa, the yield strength is 201MPa, and the elongation is 38.8%. The tensile strength of the 700℃-1h isothermal quenched Fe35Ni35Cr20Mn10Ti6 high entropy alloy is 1043MPa, the yield strength is 876MPa, the yield strength is increased by 336%, and the high elongation of 14.0% is maintained.

[0049] Summary of results of various embodiments:

[0050] The present invention alloys Fe35Ni35Cr20Mn10 high entropy alloy with Ti element to promote the effects of solid solution strengthening and second phase strengthening, and at the same time controls the temperature and time of isothermal quenching treatment, regulates the organizational morphology of the secondary phase and the matrix, and improves the comprehensive mechanical properties of the high entropy alloy. Compared with the cast Fe35Ni35Cr20Mn10 high entropy alloy, Example 4 uses 1100℃×20h high temperature homogenization treatment + 700℃×1h isothermal quenching treatment to increase the tensile strength of the alloy to 1043MPa (increase of 153%), and the yield strength to 876MPa (increase of 336%), which has excellent comprehensive mechanical properties and achieves toughness. The following Table 1 is the tensile performance data of the high entropy alloys of Examples 1 to 5.

[0051] Table 1

[0052]

Claims

1. A high-strength and high-toughness dual-phase high-entropy alloy, characterized in that: Contains metal elements Fe, Ni, Cr, Mn and Ti.

2. The high-strength and toughness dual-phase high-entropy alloy according to claim 1, characterized in that: The high-strength and toughness dual-phase high-entropy alloy is expressed as Fe35Ni35Cr20Mn10Ti6, and the numbers represent the molar ratio of each element.

3. The high-strength and toughness dual-phase high-entropy alloy according to claim 1, characterized in that: The alloy has a tensile strength of 1043 MPa, a yield strength of 876 MPa, and an elongation of 14.0%.

4. A method for preparing a high-strength and tough dual-phase high-entropy alloy as claimed in claim 1 or 2, characterized in that: The following steps are involved: Step 1: weigh the mass of each element and prepare the ingredients according to the alloy element molar ratio of Fe:Ni:Cr:Mn:Ti=(34~36):(34~36):(19~21):(9~11):(5~7); Step 2: placing the raw materials prepared in step 1 into a vacuum arc furnace in a high-purity argon environment for smelting, or smelting in a vacuum induction furnace, and cooling and solidifying in a mold to obtain an alloy ingot; Step 3: performing high temperature homogenization treatment on the alloy ingot obtained by smelting in step 2; Step 4: The alloy ingot subjected to high temperature homogenization treatment in step 3 is rapidly cooled from the homogenization temperature to the set temperature for isothermal quenching treatment, and then water quenched to room temperature after a specified time to obtain a high-strength and toughness dual-phase high-entropy alloy.

5. The method for preparing a high-strength and tough dual-phase high-entropy alloy according to claim 4, characterized in that: In step 2, the casting mold includes but is not limited to a copper mold.

6. The method for preparing a high-strength and tough dual-phase high-entropy alloy according to claim 4, characterized in that: In step 3, the temperature of the high temperature homogenization treatment is 1050-1150° C., the insulation time is 15-25 hours, and the gas environment is air.

7. The method for preparing a high-strength and tough dual-phase high-entropy alloy according to claim 4, characterized in that: In step 4, the set temperature is 650-750°C and the insulation time is 0.5-1.5h.

Citation Information

Patent Citations

  • High-entropy alloy with dispersion nano-sized precipitate strengthening effect and preparing method thereof

    CN104694808A

  • Toughened high-entropy alloy and preparation method thereof

    CN116103557A